An interval training method for racing cyclists - Firth, M. (Coaching News, 1987)
Indoor simulated cycling training appears to be a valid training method which complies with the principle of the specificity of training. If the system is calibrated it permits measures to be taken of the work load imposed upon the subjects during each training session, for the work load to be modified according to individual needs, and for it to be compared with race performances during the same period. The use of intermittent work training methods allows the subjects to tolerate greater work loads than normally met in the course of competition. Thus the training method follows the principle of progressive overload.